Cognitive-Enhancing, Ex Vivo Antilipid Peroxidation and Qualitative Phytochemical Evaluation of the Aqueous and Methanolic Stem Bark Extracts of Lonchocarpus eriocalyx (Harms.) - Gervason Moriasi; Anthony Ireri; Mathew Ngugi (Biochemistry Research International)
Over 50 million persons are living with cognitive deficits worldwide, with over 80% of these individuals living in the developing world. The number of affected persons is projected to go over 152 million by the year 2050. Current drugs used for cognitive impairment are debatably ineffective, costly, inaccessible, and associated with undesirable events that call for the search for alternative and complementary approaches. Plants are arguably affordable, accessible, and efficacious. However, despite the reported healing claims, scientific data validating these claims are lacking. L. eriocalyx is traditionally used for the management of various conditions, including cognitive impairment but has not been scientifically explored. In this study, the Morris Water Maze (MWM) method was used to evaluate in vivo cognitive-enhancing effects of studied extracts of L. eriocalyx. Furthermore, following MWM experiments, brains were dissected and processed, and malondialdehyde profiles were determined. Qualitative phytochemical profiles of the studied plant extracts were also determined. The results showed that mice that were treated with the studied plant extracts took significantly shorter transfer latencies, navigation distances, and significantly longer latencies in the target quadrant (NW) (p<0.05) compared with the negative control mice, indicating cognitive-enhancing activities. Furthermore, cognitively impaired mice that received the studied plant extracts had significantly lower MDA profiles compared with the MDA profile of the negative control group mice (p<0.05). The cognitive-enhancing and MDA profile lowering effects were attributed to the presence of antioxidant phytoconstituents that ought to have modulated the redox state, thereby attenuating brain damage. These extracts can be, therefore, used for the management of cognitive deficits. Further studies leading to isolation and characterization of active molecules for cognitive impairment are recommended. Furthermore, the precise mechanism(s) through which these extracts exert their pharmacologic activity should be established.